Analysis of the Current Development Status of Hydrogen-based New Energy Vehicle Energy Systems - Zhong, Kaiming (International Journal of Mechanical and Electrical Engineering, 2024)
This study is focused on exploring the optimization of performance and sustainable development of hydrogen-based new energy vehicle systems. By taking into account critical factors such as hydrogen production, storage, fuel cell systems, and overall vehicle power systems, the objective is to enhance energy efficiency and mitigate environmental impact. The advancement of hydrogen vehicle technology is pivotal in achieving these goals. Hydrogen, recognized as a clean and plentiful energy source, holds potential for reducing greenhouse gas emissions and lessening reliance on fossil fuels within the transportation sector. The effective integration of efficient hydrogen production methods, dependable storage technologies, and cutting-edge fuel cell systems is essential for fully realizing the benefits of hydrogen-powered vehicles. These vehicles operate with zero emissions and can significantly contribute to addressing challenges related to climate change and urban air quality. Through this research, our aim is to contribute to ongoing efforts in developing sustainable transportation solutions. By optimizing the entire hydrogen energy chain—from production through to vehicle operation—we seek to maximize the advantages of hydrogen technology while minimizing its environmental footprint. This interdisciplinary approach merges engineering, environmental science, and policy analysis to pave the way toward a cleaner and more sustainable future for automotive transportation.